Examining the opinions of senior university students and their actual clients regarding the supervision of practice-based course structured on the Balance model of Positive Psychotherapy - Ekin Özbey Duygu (The Global Psychotherapist)
Positive psychotherapy is one of the most comprehensive and effective therapeutic methods in psychoanalytic models. The Balance model of Positive psychotherapy is a key concept that helps not only psychotherapists and clients to detect the problem to plan a route for action but also to build hope for the future life. The study aims to examine the effectiveness of the supervision process of a practical module, “Psychological Counseling with an Individual,” structured on the Balance model of Positive psychotherapy on university students having the module and their actual clients. There were 12 senior-year university students and 12 clients in the supervision process. Evaluation forms for students and clients comprised by the author were used as collection tools. The outcomes showed that including the Balance model in the sessions helped understand the psy